2018
DOI: 10.17511/jopm.2018.i01.06
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of hysterectomy specimens in tertiary care center: two year study

Abstract: Background: The uterus is a major female hormone-responsive reproductive pear-shaped organ located within the pelvic region. The gross morphology of uterus quite dramatically changed throughout life by changing levels of ovarian hormones. A hysterectomy is done for many reasons including the ridding of tumours both benign and malignant. It is the most commonly performed gynecological surgical procedure throughout the world. Materials and Methods: This study was undertaken to identify the different types of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
3
2
0
Order By: Relevance
“…The most common reason for hysterectomy in our study was uterine fibroids, which is consistent with previous reports in the literature [3,13,19,20,21] . Histopathological examination of…”
Section: Discussionsupporting
confidence: 93%
“…The most common reason for hysterectomy in our study was uterine fibroids, which is consistent with previous reports in the literature [3,13,19,20,21] . Histopathological examination of…”
Section: Discussionsupporting
confidence: 93%
“…9,10 The commonest surgical approach was abdominal hysterectomy (60.8%) followed by vaginal hysterectomy (39.2%) ratio being 1.5 which is similar to other studies. 11,12 The peak age incidence of patients was 41-50 years, while the mean parity was 4, such figures are comparable to those reported in previous studies. [12][13][14] This is because the frequency of most common indication for abdominal hysterectomy i.e.…”
Section: Discussionsupporting
confidence: 88%
“…11,12 The peak age incidence of patients was 41-50 years, while the mean parity was 4, such figures are comparable to those reported in previous studies. [12][13][14] This is because the frequency of most common indication for abdominal hysterectomy i.e. leiomyoma, adenomyosis peak in the age group 31-50yr.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patel et al and Rather et al reported chronic cervicitis in 28.1% and 89.3% cases respectively. 10,14 Ten (2.10%) cases of squamous cell carcinoma of the cervix were detected in this study. This finding is comparable to that reported by Patel et al 14…”
Section: Discussionmentioning
confidence: 45%